2018
DOI: 10.1002/adma.201804657
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Organized Poly(vinylpyrrolidone)‐Based Cathode Interlayer in Inverted Fullerene‐Free Organic Solar Cells

Abstract: surface of the film, forming the interlayer and active layer simultaneously. In order to better distinguish, the two approaches are recognized as the step-by-step preparation method and the self-organization method, respectively, in this work. The self-organization method not only simplifies the fabrication procedure significantly but also makes the tolerance of the interlayer to thickness variation no need consideration. And hence, intensive investigations have been focused on the self-organization method in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Moreover, the integral current density values deduced from EQE spectra match well with those obtained from the J–V measurements (Table ). The PCEs of one‐step fullerene/NF OSCs fabricated by doctor blade in previous reports are presented in Figure c . It can be seen that our one‐step doctor‐bladed OSCs with a conventional NF system show the very high PCEs among the reported results, due to the optimized electrical property of IL through SVA.…”
Section: Solar Cell Parameters Of Pbdb‐t:it‐m Devices By Doctor‐bladementioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, the integral current density values deduced from EQE spectra match well with those obtained from the J–V measurements (Table ). The PCEs of one‐step fullerene/NF OSCs fabricated by doctor blade in previous reports are presented in Figure c . It can be seen that our one‐step doctor‐bladed OSCs with a conventional NF system show the very high PCEs among the reported results, due to the optimized electrical property of IL through SVA.…”
Section: Solar Cell Parameters Of Pbdb‐t:it‐m Devices By Doctor‐bladementioning
confidence: 54%
“…The PCE of one‐step printing type‐I device with SVA treatment is 38% higher than 8.05% of type‐I device without SVA. To the best of our knowledge, the obtained PCE value of >11% is one of the highest values reported to date for one‐step printed OSCs featuring a self‐assembled IL . For comparison, two‐step doctor‐blade printing OSC was also produced with varying PFN thickness, substrate temperature as well as SVA treatment (Figure S4–6, Table S4–6, Supporting Information).…”
Section: Solar Cell Parameters Of Pbdb‐t:it‐m Devices By Doctor‐bladementioning
confidence: 84%
“…The contact angle of the biocomposite can reect the wetting properties of the material, [30][31][32][33] while the wetting performance is directly related to the wear of the material surface. The results of contact angle studies are shown in Fig.…”
Section: Contact Angle Studiesmentioning
confidence: 99%
“…Promoted by the prosperous development of small molecular nonfullerene acceptors and diverse donor materials, the power conversion efficiencies (PCE) of polymer solar cells have exceeded 14%, suggesting the bright promise of PSCs in practical applications . Moreover, device optimization including interfacial and device engineering also plays a crucial role in promoting the development of PSCs . Nevertheless, restrained by the prerequisite molecular energy level differences of the donor and acceptor materials, the conventional binary PSCs built with one donor–acceptor pair can hardly harvest the solar photons as much as possible in a wide range of solar spectrum .…”
Section: Introductionmentioning
confidence: 99%